Analis Faktor Kelengkapan Produk, Kualitas Produk, Citra Produk, dan Tempat Terhadap Loyalitas Konsumen Pada Toko Aini Fashion Kotapinang - Almira, Mahsya Dwi (Universitas Labuhanbatu, 2021)
The purpose of this study was to determine the influence of promotional locations, facilities and service quality on the decision to use Aini fashion store Kotapinang District Kotapinang South Labuhanbatu Regency either partially or simultaneously. The sample in this study amounted to 34 people, namely consumers at Aini fashion store Kotapinang. Techniques in determining this sample using census Sampling, where the technique of determining the sample used if the sample is less than 100 where all people/consumers are sampled, so the number of research samples is 34 people. The analysis method used is descriptive analysis, classical assumption test, multiple linear regression analysis, t test, F test, and coefficient of determination and this data is processed using IBM SPSS Statistics 26 program. The results of the hypothesis test showed that the partial completeness of the product has a positive and significant effect on consumer loyalty, it is seen from the value of thitung for product completeness is thitung 2.718 > ttable 1.697, with a significant value of 0.102 < 0.05.Â Partially the quality of the product has a positive and significant effect on consumer loyalty, it is seen from the value of thitung for completeness of the product is thitung 1.931 > ttable 1.697, with a significant value of 0.193 < 0.05. Partially the image of the product has a positive and significant effect on consumer loyalty, it is seen from the value of thitung for completeness of the product is thitung 1.854 > ttable 1.697, with a significant value of 0.140 < 0.05. Partially place positive and significant effect on consumer loyalty, it is seen from the value of thitung for product completeness is thitung 2.909 > ttable 1.697, with a significant value of 0.171 < 0.05. Ftable value in the distribution 4: 29 is 2.70, then based on Table 4.14 it is seen that the value of Fhitung 11.183 > 2.70, and the significant value of 0.039< 0.05, this shows that simultaneously The Independent Variable has a positive and significant effect on the Dependent variable.Â